(untitled) - Maitra, Gitin M. (New Delhi, 1994)
This book provides extensive information on various aspects of gears and gearing systems. It contains enough tables, illustrative examples and diagrams. It is based on ISO specifications and is a unique blend of practical as well as theoretical aspects of gear designs. It also includes more on spiral bevel gears, arcoid gears, klingelnberg and gleason systems and gear tooth checking
Keywords: Gearing,Machine parts,Mechanical engineering